2015
DOI: 10.1016/j.psyneuen.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

HPA-axis reactivity interacts with stage of pubertal development to predict the onset of depression

Abstract: Both elevated and blunted levels of cortisol secretion during childhood and adolescence have been linked to the subsequent onset of Major Depressive Disorder (MDD). These mixed findings may be due to developmental changes in HPA-axis functioning, which have not been previously assessed in the context of risk. In the present study, therefore, we examined whether pubertal development moderated the influence of cortisol secretion on the subsequent development of MDD. Eighty-nine never-disordered girls ages 9-15 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 32 publications
(39 reference statements)
3
72
1
Order By: Relevance
“…This is consistent with a lately published study which showed that the onset of MDD was predicted by cortisol hyporeactivity in girls who were earlier in pubertal development [14]. The authors proposed that both elevated stress reactivity and blunted cortisol secretion appear to be risk factors for the development of depression.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a lately published study which showed that the onset of MDD was predicted by cortisol hyporeactivity in girls who were earlier in pubertal development [14]. The authors proposed that both elevated stress reactivity and blunted cortisol secretion appear to be risk factors for the development of depression.…”
Section: Discussionsupporting
confidence: 90%
“…15 Youth at different pubertal stages may differ in their HPA-axis functioning. 35 Such differences in the HPA-axis functioning may further be associated with their ability to regulate negative emotion associated with the stressful events. 35 Colich and colleagues (2015) have found that blunted cortisol reactivity to a laboratory-based stressor task predicted MDD onset in adolescent girls in early puberty.…”
Section: Discussionmentioning
confidence: 99%
“…35 Such differences in the HPA-axis functioning may further be associated with their ability to regulate negative emotion associated with the stressful events. 35 Colich and colleagues (2015) have found that blunted cortisol reactivity to a laboratory-based stressor task predicted MDD onset in adolescent girls in early puberty. 35 However, the effect was reversed for girls in the later pubertal stages, with elevated cortisol reactivity predicting MDD onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related persistent hypersecretion of corticotropin-releasing factor, overproduction of adreno-corticotropic hormone and increased glucocorticoid secretion causes reduced neurogenesis in the hippocampus, which has been related to adolescent and adult depression (45). In females, the effect of cortisol reactivity on the subsequent onset of MDD is influenced by the levels of gonadal steroid hormones associated with pubertal development (46) and early puberty seems to increase the risk of depression in girls (29, 47). Importantly, the earlier onset of puberty, which has been observed, first in USA and now in Europe, coincides with the increasing prevalence of adolescent depression (48).…”
Section: Endocrinal Metabolic and Immunological Mechanismsmentioning
confidence: 99%